Making Localization Work: The Everyday Practice of Three NGOs in South Sudan and Northern Uganda - Dijkzeul, Dennis (Frontiers in Political Science, 2021)
In humanitarian action, localization can be characterized by high hopes, many disillusions, and only limited progress. This is partly because traditional humanitarian action focuses mostly on short-term action and is supply-oriented, with decisions on the set-up and evaluation of aid activities being made by outside donors and organizations, instead of by the beneficiaries/target groups themselves. After a theoretical overview of localization and its problems, this article describes how two South Sudanese NGOs, Mary Help Association (MHA) and Bishop Gassis Relief and Rescue Foundation (BGRRF), and a Ugandan NGO, Caritas Gulu, work on food security. It describes how they are implementing a three-year program with support from Caritas Germany. The article analyzes the importance of their long-term interaction to foster trust over time through capacity development. Such capacity development includes capacity building (e.g., training, joint workshops, regular evaluations, and audits) and capacity sharing in the form of South-South cooperation. This analysis also shows that localization can be strengthened when the involved organizations agree on goals, and establish a process to reinforce their cooperation by strengthening the activities on the ground to achieve those goals. It also indicates the role of religion within capacity-development, as well as the structural problems in the context of localization that cannot easily be overcome. A conceptual model summarizes the analysis and explains the degree to which localization can be successful. Finally, the conclusions summarize the main arguments and indicate issues for further research.